High‐intensity training in normobaric hypoxia enhances exercise performance and aerobic capacity in Thoroughbred horses: A randomized crossover study - Mukai, Kazutaka (Physiol Rep, 2020)
We examined the effects of high‐intensity training in normobaric hypoxia on aerobic capacity and exercise performance in horses and the individual response to normoxic and hypoxic training. Eight untrained horses were studied in a randomized, crossover design after training in hypoxia (HYP; 15.0% inspired O(2)) or normoxia (NOR; 20.9% inspired O(2)) 3 days/week for 4 weeks separated by a 4‐month washout period. Before and after each training period, incremental treadmill exercise tests were performed in normoxia. Each training session consisted of 1 min cantering at 7 m/s and 2 min galloping at the speed determined to elicit maximal oxygen consumption ( [Formula: see text] O(2)max) in normoxia. Hypoxia increased significantly more than NOR in run time to exhaustion (HYP, +28.4%; NOR, +10.4%, p = .001), [Formula: see text] O(2)max (HYP, +12.1%; NOR, +2.6%, p = .042), cardiac output ( [Formula: see text]; HYP, +11.3%; NOR, −1.7%, p = .019), and stroke volume (SV) at exhaustion (HYP, +5.4%; NOR, −5.5%, p = .035) after training. No significant correlations were observed between NOR and HYP for individual changes after training in run time (p = .21), [Formula: see text] O(2)max (p = .99), [Formula: see text] (p = .19), and SV (p = .46) at exhaustion. Arterial O(2) saturation during exercise in HYP was positively correlated with the changes in run time (r = .85, p = .0073), [Formula: see text] (r = .72, p = .043) and SV (r = .77, p = .026) of HYP after training, whereas there were no correlations between these parameters in NOR. These results suggest that high‐intensity training in normobaric hypoxia improved exercise performance and aerobic capacity of horses to a greater extent than the same training protocol in normoxia, and the severity of hypoxemia during hypoxic exercise might be too stressful for poor responders to hypoxic training.